Fostering foreign languages learning through music : music beyond its instrumentalization (2022)
The purpose of this research is to critically analyze the usage of music in foreign languages classes, such as the benefits it brings to the classroom environment, cognitive and emotional effects that music provokes in foreign language students and some disadvantages the usage of music can bring to the classroom. Music is an essential element to a foreign language class, since its usage increases memory capacity, attention, and concentration, it stimulates creativity and child-like imagination (Berrío, 2011). Music is a tool that helps to easily learn a foreign language in a nice way students have fun (Bustamente, 2016), students can improve speaking skills by listening activities (Pérez, 2010), low affective filters and music achieves different multiple intelligences. Music increases motivation, concentration and generates a good atmosphere, it decreases stress and introduces cultural aspects of a foreign language (Ruiz Calatrava, 2016). Finally, Lake (2002) states that music is more than just words and notes on paper, music is an environment that expresses emotion and conveys a message. Lake remarks that music is the most potent instrument for education. Due to the reasons presented before, it is important to think critically about the usage of music in the classroom. It is crucial to create an effective environment to use music in a foreign language class, because many factors can positively or negatively affect the class, for example, the genre of the song, the complexity of the lyrics, the pre, while and post task for instance.